Policy options for inducing a supply response - Takeshima, Hiroyuki (University of Pennsylvania Press, 2016)
The objective of this chapter is to examine empirically some of the key economic factors affecting the profitability of paddy rice production at the farm level and, given these current conditions, estimate whether price incentives are able to induce an aggregate supply response at the national level. The types of public-sector interventions needed to promote output growth are also explored, drawing on lessons and experiences from other major rice-producing regions in the developing world. The chapter specifically focuses on irrigated and lowland production systems because, as shown in Chapter 3, these systems have the greatest potential for rice-production growth in Nigeria. Understanding the microeconomics of these systems can provide important insights into the constraints affecting rice-production growth, despite recent government efforts to introduce price incentives through higher import tariffs.